ARTICULAR CARTILAGE REGENERATION : A SYSTEMATIC REVIEW - Susilo, Dhanang (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Articular cartilage is a highly specialised type of connective tissue found in bones-joints. Its primary function is to provide a smooth, lubricated surface for movement and to reduce the coefficient of friction to facilitate movement. Regenerative medicine has been developed in recent years as an alternative to conventional surgery. The objective is to create a new tissue that is as similar as feasible to the existing cartilage. Due to the close relationship between tissue structure and composition and function, it is believed that the capacity to reconstruct structure is essential for regeneration. Regenerative medicine has become one of the most fascinating areas of biotechnology through the use of cell and gene therapy and tissue engineering. This has given researchers, physicians, and patients a great deal of optimism. The primary objective of advances in this field is to heal damaged tissue, not to supplant it with an external device. In the future, grafts and artificial prostheses may not be necessary.